Evaluation on Biofilter in Recirculating Integrated Multi-Trophic Aquaculture - S. Sumoharjo; Asfie Maidie (Chemical Engineering Diponegoro University, 2013)
Integrated multi-trophic aquaculture pays more attention as a bio-integrated food production system that serves as a model of sustainable aquaculture, minimizes waste discharge, increases diversity and yields multiple products. The objectives of this research were to analyze the efficiency of total ammonia nitrogen biofiltration and its effect on carrying capacity of fish rearing units. Pilot-scale bioreactor was designed with eight run-raceways (two meters of each) that assembled in series. Race 1-3 were used to stock silky worm (Tubifex sp) as detrivorous converter, then race 4-8 were used to plant three species of leaf-vegetable as photoautotrophic converters, i.e; spinach (Ipomoea reptana), green mustard (Brassica juncea) and basil (Ocimum basilicum). The three plants were placed in randomized block design based on water flow direction. Mass balance of nutrient analysis, was applied to figure out the efficiency of bio-filtration and its effect on carrying capacity of rearing units. The result of the experiment showed that 86.5 % of total ammonia nitrogen removal was achieved in 32 days of culturing period. This efficiency able to support the carrying capacity of the fish tank up to 25.95 kg/lpm with maximum density was 62.69 kg/m3 of fish biomass productionDoi: http://dx.doi.org/10.12777/ijse.4.2.2013.80-85 [How to cite this article: Sumoharjo, S. and Maidie, A. (2013). Evaluation on Biofilter in Recirculating Integrated Multi-Trophic Aquaculture. International Journal of Science and Engineering, 4(2),80-85. Doi: http://dx.doi.org/10.12777/ijse.4.2.2013.80-85]